The Bible : in the beginning [videorecording (DVD)] - Parks, Michael, 1940-2017; Bergryd, Ulla, 1942-2015; Harris, Richard, 1930-2002; Huston, John, 1906-1987; Huston, John, 1906-1987; Boyd, Stephen, 1931-1977; Scott, George C., 1927-1999; Gardner, Ava, 1922-1990; O'Toole, Peter, 1932-2013; Sallis, Zoë; Ferzetti, Gabriele, 1925-2015; Rossi-Drago, Eleonora, 1925-2007; et al. (Cinema classics collection., 2005)
Depicts the first 22 chapters of Genesis on an epic scale, including the story of man's creation, his fall, his survival, and his indomitable faith in the future.